The Semantics of Language and Speech in Idiolect and Sociolect - Labaszczuk, Michał (Respectus Philologicus, 2006)
The article focuses on the problem of the relation between language and speech, taking into account the problem of the semantics of language and speech of lexical units. This problem is overburdened by the necessity of taking notice of the traditional dichotomy of idiolect and sociolect. The article revises the concepts of language, speech and speech practice, which were proposed by F. De Saussure in accordance with the contemporary anthropocentric paradigm of linguistics. The concepts of idiolect and sociolect, which are modified a little, are the key notions of the article. The proposed emphasis on the noted terms is related to an attempt to accentuate idiolect and point out the necessity of a methodological approach to researching the facts of language and speech on the basis of the concept of "idiolect" while sociolect is conceived just as the construct of sociocentric approach to the linguistic research in science.